Comparison of Surface Defects in Different Rotary Files: An in-Vitro Study - Krish Chopra; Nidambur Vasudev Ballal (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the surface defects in Wave One Gold and Jizai rotary files after 1 and 3 uses. Material and Methods: Ninety-six resin blocks with stimulated canals and 12 files per system were used. The files were pre-examined under scanning electron microscopy (SEM) to exclude files with pre-existing cracks and craters. Instrumentation and SEM evaluation of the files were performed after 1 and 3 uses, respectively. Two independent operators analyzed the images, and scoring was carried out for each file's coronal, middle, and apical thirds. The surface defects at different thirds of the file systems were analyzed using the Chi-Square test and Kendel Tau's test. Results: After one use, both the file systems did not produce any significant surface defects in the coronal, middle, and apical thirds. However, after three uses, there was minor plastic deformation in the coronal and middle thirds of the Wave One Gold file system. Jizai file system did not produce any surface defects in the coronal, middle, and apical thirds. Conclusion: After one use, no surface defects were created in Wave One gold and Jizai rotary files. Wave One Gold exhibited more significant surface defects after three uses in the coronal and middle thirds.